Responding to problematic sexual behaviours of primary school children: supporting care and education staff. Issue 1 (2nd January 2020) - McInnes, Elspeth; Ey, Lesley-Anne
ABSTRACT: Early childhood and primary educators' and carers' education and support in identifying and responding appropriately to children displaying problematic sexual behaviours has fallen behind the demands currently arising in care and education sites in Australia. This is a key finding of research examining professional educators' and carers' experiences of problematic sexual behaviours in their workplaces, their understanding of problematic sexual behaviours, and their source of training in this area. This paper reports on the professional development, workplace and community support for educators and affected children, which educators and carers wanted to have implemented to more adequately respond to their professional needs and the needs of affected children and their families. The research was conducted using an online survey in 2016 and involved 107 respondents from government, independent and Catholic primary schools, preschools and care organisations.